GEM-2 ice and platelet total thickness measurements for transect AFIN_ATKA_20221122 - Mara Neudert; Stefanie Arndt (PANGAEA, 2025)
The snow+ice thickness (distance from the snow surface to the consolidated ice-platelet ice interface) and the underlying platelet ice thickness was measured by the electromagnetic induction (EM) method. On all transects, we used a multi-frequency EM instrument sensor (GEM-2 by Geophex Ltd) towed on a small sled behind a snowmobile (Hunkeler et al, 2016b). The instrument includes a real-time data processing unit including a GPS receiver which communicates with a pocket PC that is operates the sensor and records the EM and GPS data streams. The GEM-2 is a multi-frequency sensor that can transmit multiple configurable frequencies in the kHz range simultaneously. The sensor setup during AFIN used 5 frequencies with an approximately logarithmic spacing throughout the frequency range of the sensor (1.53, 5.31, 18.33, 63.03, and 93.09 kHz). The transect measurements are based on a sensor calibration, where the GEM-2 was placed in a zero-conductivity environment on the ice shelf before and after each transect to correct for signal offsets in instrument drift. The snow+ice and platelet ice thickness and conductivity retrieval of the calibrated GEM-2 surveys data was done by multi-frequncy inversion in the modified framework of the EMagPy (McLachlan et al., 2020) accounting for the bucking coil bias (Hunkeler at al., 2016a). To validate the retrieved thicknesses, we used the snow depth, ice thickness and platelet ice thickness from the drill hole measurements coincident with the GEM-2 transects. The coincident drill hole data can be found here: doi:10.1594/PANGAEA.968459. For more details we refer to the paper by Neudert et al, 2024: Improved sub-Ice Platelet Layer Mapping with multi-frequency EM Induction Sounding, in review at Journal of Applied Geophysics, Elsevier.
In: Neudert, M; Arndt, S (2025): GEM-2 ice and platelet total thickness measurements from the 2022-2023 AFIN summer campaign [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.968041